Hubungan antara Penerimaan Kelompok Teman Sebaya dengan Konsep Diri pada Remaja Panti Asuhan di Kabupaten Badung, Bali - I Gusti Agung Tri Santiari; David Hizkia Tobing (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2016)
Self concept is a reflection of the judgement of others (Charles Cooley, in Watson, Borlall-Tregerthan, & Frank, 1984). The formation of individual self concept is influenced by several factors, one of which is peers in adolescence is a very important figure for indiciduals. Not all teens get through phase of adolescence his parents. There are some situations that cause adolescent should live apart from their parents, by staying at the orphanage institution for example. This different conditions will certainly affect the processes occurring friendship with the adolescent peer groups which will certainly affect the formation of self concept. The purpose of this study was to determine the relationship between peer group acceptance of the self concept in adolescents orphanage in the District Badung, Bali.Subjects in this study were 170 adolescents (girls=101, boys=69) who lived in the orphanage which is in the District Badung-Bali. The instrument of this research are self concept and peer group acceptance scale. Self concept scale consisted of 30 item with a reliability coefficient of 0,875. Peer group acceptance scale consisted of 21 item with a reliability coefficient of 0,873.Product moment correlation analysis result showed the correlation of 0,719 with a significance level of 0,000 (p<0,05), which means that there is a significant and positive relationship between peer group acceptance and self concept in adolescents orphanage in the District Badung, Bali. The higher the intensity of the peer group acceptance, the more positive self concept in adolescents orphanage in the District Badung, Bali. Keywords : Self Concept, Peer Group Acceptance, Adolescenct, Orphanage.